HUBUNGAN ANTARA PARTISIPASI SISWA DALAM KEGIATAN EKSTRAKURIKULER PRAMUKA DENGAN SIKAP KEPEDULIAN LINGKUNGAN HIDUP - Heryanti, Erna; Matondang, M Nurdin; Wati, Diana Ambar (Biosfer: Jurnal Pendidikan Biologi, 2016)
The number of cases on the environmental damage shows low concern for the environment. Environment awareness can be improved through scouting extracurricular activities carried out in each school as an educational institution. Scouting teaches lot of value, such us leadership, togetherness, social, love of nature, and independence. The aim of this research was to know correlation level of student’s participation in scouting extracurricular with the attitude of environmental awareness. This research was conducted at Senior High School 88 Jakarta on May 2016. The method used was a correlational descriptive. Samples were selected by Purposive Random Sampling of 91 students. Prerequisite test showed that data were normal and homogeneous. Regression model showed that Ŷ=5.621+0.390X. The correlation coefficient obtained was 0.544, which means there is a correlation between student’s participation in scout extracurricular with the attitude of environmental awareness.